An Experimental Study of Permeability Characteristics of Outdoor Particles under Indoor and Outdoor Temperature Differences. (2017) - Lu, Yuxin; Qiu, Jiayi; Liu, Yanhua
Abstract: To investigate the permeability characteristics of outdoor particles and the change rules over time of I/O ratio, an experiment was designed and experiments were conducted based on an environmental room in Xi'an Jiaotong University. The concentrations of PM2.5 and PM10 in indoor-to-outdoor air were measured under the condition that the door and windows were closed and there was no indoor pollutant source. Under winter condition, four sets of temperature differences between indoor and outdoor were used, including 0℃, 5℃, 10℃ and 15℃.The experimental results indicated that: (1) Indoor and outdoor temperature differences affected significantly the permeability characteristics of outdoor fine particles. (2) With the increasing of temperature difference, more outdoor particles penetrated into the room. (3) The concentration variation of PM2.5 and PM10 in indoor air was consistent in general under the same temperature difference. (4) The temperature difference influenced the I/O ratio, and the influence on PM2.5 was greater than that on PM10.